Second-Hand Family - Parker, Richard (USA SCHOLASTIC BOOK SERVICES, 1969)
A twelve-year-old boy goes to a new foster home where he is confronted with a bossy girl his age, a surly older boy who is a rock and roll player, a sick father, and a mother with a quick temper.
Keywords: Children Literature